Confinement of the 0.5…4.5 keV plasma ions in low density discharges of the U-3M torsatron - Dreval, M.; Slavnyj, A.S. (Вопросы атомной науки и техники, 2012)
Dependences of the charge exchange (CX) fluxes of neutral are investigated via neutral particle analyzers (NPA) in the U-3M torsatron. Fast (≤0.5 ms) decay of the vertical and tangential CX fluxes has been observed after turning off RF heating power. According to these measurements, the U-3M energy confinement time of the 0.5…4.5 keV ions is less than 0.5 ms in the low density (ne=(1…4)·10¹² cm⁻³) discharges. No difference between confinement of the ion energy component parallel to the magnetic field and confinement of the perpendicular to the magnetic field one was observed in U-3M. Evidently, an ion cooling through CX collisions with neutrals sustain the main channel of the 0.5…4.5 keV ion energy loss in the U-3M torsatron.